(untitled) (Journal of Fiber Bioengineering and Informatics, 2016)
Degenerative changes and foot deformities are common when people get older. Foot deformities, such as hallux valgus, bunionettes and pes planus, are commonly found among older people, which may lead to changes in foot anthropometry. A decline in functional mobility and greater risk of falling are linked to foot deformities and footwear. This study therefore aims to evaluate the anthropometric measurements between healthy and deformed feet in order to determine the key foot measurements in relation to the deformed foot which can also act as indicators in current footwear sizing systems. By using a 3D hand- held scanner, 11 foot anthropometric measurements are captured and used to characterise the dimensions and foot shape between healthy and deformed feet. A total of 49 elderly people between the ages of 65-95 years old, including 41 women and 8 men (mean: 81.71; SD: 7.08) are recruited for this study. The results indicate that the foot characteristics of elderly people with foot deformities are different from those without deformities, especially in the larger deformity of the degree of hallux valgus and increased width of the ball for women, and higher instep height for men. The length of the foot and ball, width and girth of the ball, and degree of hallux valgus deformity are common predictors for differentiating between healthy and deformed feet. It is also found that the current footwear sizing systems fail to accommodate the foot dimensions of elderly people in both foot length and width, which may therefore lead to foot discomfort and even limit their daily life activities.